Amorphous CdO‐In2O3 Electrode for Perovskite‐Based Bifacial and Tandem Photovoltaic Technologies with High Energy Production. Issue 1 (19th November 2021) - Cheng, Yuanhang; Zeng, Zixin; Liu, Tianyuan; Wang, Ying; Rodríguez-Gallegos, Carlos D.; Liu, Haohui; Liu, Xixia; Thway, Maung; Khup, David; Khaing, Aung Myint; Yu, Kin Man; Tsang, Sai-Wing; et al.
Abstract : Energy production of perovskite‐based photovoltaic (PV) technology can be increased not only by improving device efficiency of perovskite solar cells (PVSCs) but also by innovative concepts such as bifacial and tandem configurations which require low‐damage and highly transparent top electrodes. Herein, an amorphous CdO‐In2 O3 alloy film with high transparency and low resistivity and its application in a bifacial PVSC and a perovskite/Si 4T tandem solar cell are reported. Due to the high optical transmittance, the CdO‐In2 O3 ‐based PVSC shows a high bifaciality factor of 84.0%, and the CdO‐In2 O3 ‐based perovskite/Si 4T tandem solar cell achieves a champion power conversion efficiency of 25.12%, much higher than the indium tin oxide based tandem cell. Finally, a yearly energy yield calculation and levelized cost of energy (LCOE) analysis for these PV technologies (together with Si single‐junction solar cells as a reference) in Singapore, Australia, and Germany are conducted. The results demonstrate the potential of CdO‐In2 O3 ‐based perovskite PV technologies, yet more efforts are still required to further reduce the manufacturing cost to achieve competitive LCOE values in countries with relatively low PV installation cost. Abstract : An amorphous CdO‐In2 O3 layer is developed by room‐temperature sputtering technique. Thanks to the optical transmittance, CdO‐In2 O3 shows promising potential in the application of perovskite‐based bifacial and tandem solar cells. The semitransparent perovskite solar cell exhibits a high bifaciality factor of 84.0%, and the 4T perovskite/Si tandem cell exhibits an efficiency of 25.12%.